Construction of an indicator framework for vaccine inclusion in public health programs: A Delphi-entropy method study - Qing Wang; Peixi Dai; Mengmeng Jia; Mingyue Jiang; Juan Li; Weizhong Yang; Luzhao Feng (Taylor & Francis Group, 2023)
ABSTRACTGovernments must decide which vaccine priority to include in their public health programs. Using the modified Delphi and entropy method, we developed an indicator framework for vaccine inclusion at the national, provincial, municipal, and district/county levels, each containing three dimensions. In total, 4 primary indicators, 17 secondary indicators, and 45 tertiary indicators were selected, covering vaccine-preventable diseases, candidate vaccines, and social drivers of the supply and demand sides. From a subjective perspective, there was no significant weighting difference in the primary and secondary indicators at all administrative levels. "Vaccine-preventable diseases" as a primary indicator had the greatest weight in the peer group, of which "Health burden" had the highest weight among the secondary indicators. From the objective perspective, the social drivers on the supply and demand sides of the primary indicators accounted for 65% and higher. Among the secondary indicators, "the characteristics of the candidate vaccine" and "vaccine-related policies on the supply side" held 8% of weights or more at both national and provincial levels. "Demographic characteristics" held the highest weight at the municipal (13.50) and district/county (15.45) level. This study indicates that China needs different considerations when using WHO-recommended vaccines at the national, provincial, municipal, and district/county levels. In addition, this study highlights that behavioral and social drivers are important indicators that need to be considered for decision-making. This framework provides a tool for policymakers to determine the inclusion priority of candidate vaccines.